Prolactin and oxytocin: potential targets for migraine treatment - Szewczyk, Anna K; Ulutas, Samiye; Aktürk, Tülin; Al-Hassany, Linda; Börner, Corinna; Cernigliaro, Federica; Kodounis, Michalis; Lo Cascio, Salvatore; Mikolajek, David; Onan, Dilara; Ragaglini, Chiara; Ratti, Susanna; et al. (The journal of headache and pain, 2023)
Migraine is a severe neurovascular disorder of which the pathophysiology is not yet fully understood. Besides the role of inflammatory mediators that interact with the trigeminovascular system, cyclic fluctuations in sex steroid hormones are involved in the sex dimorphism of migraine attacks. In addition, the pituitary-derived hormone prolactin and the hypothalamic neuropeptide oxytocin have been reported to play a modulating role in migraine and contribute to its sex-dependent differences. The current narrative review explores the relationship between these two hormones and the pathophysiology of migraine. We describe the physiological role of prolactin and oxytocin, its relationship to migraine and pain, and potential therapies targeting these hormones or their receptors.In summary, oxytocin and prolactin are involved in nociception in opposite ways. Both operate at peripheral and central levels, however, prolactin has a pronociceptive effect, while oxytocin appears to have an antinociceptive effect. Therefore, migraine treatment targeting prolactin should aim to block its effects using prolactin receptor antagonists or monoclonal antibodies specifically acting at migraine-pain related structures. This action should be local in order to avoid a decrease in prolactin levels throughout the body and associated adverse effects. In contrast, treatment targeting oxytocin should enhance its signalling and antinociceptive effects, for example using intranasal administration of oxytocin, or possibly other oxytocin receptor agonists. Interestingly, the prolactin receptor and oxytocin receptor are co-localized with estrogen receptors as well as calcitonin gene-related peptide and its receptor, providing a positive perspective on the possibilities for an adequate pharmacological treatment of these nociceptive pathways. Nevertheless, many questions remain to be answered. More particularly, there is insufficient data on the role of sex hormones in men and the correct dosing according to sex differences, hormonal changes and comorbidities. The above remains a major challenge for future development.
Keywords: Migraine Disorders; receptory oxytocinu; Prolactin; Sex differences; analgetika; Gonadal Steroid Hormones; lidé; PRLR; Oxytocin; Receptors, Oxytocin; Female; prolaktin; oxytocin; Migraine; Male; pohlavní steroidní hormony; ženské pohlaví; Pain; Humans; mužské pohlaví; receptory prolaktinu; bolest; Hormones; Analgesics; OTR; migréna; Receptors, Prolactin